Representation of Women’s Struggle in Red Snake: Sister in Arms Film - Saninah, Dhiyaul; Dewi M, Jonathan Irene Sartika; Prafitri, Wilma (General English Education, 2025)
Feminism is a movement advocating for gender equality in society, addressing issues that impact women, and against gender-based violence and harassment. This study examines the gender conflicts faced by female characters in the film Red Snake Sister in Arms. This study seeks to elucidate the challenges faced by women shown in the film Red Snake Sister in Arms. The depiction of gender conflict illustrates women's efforts to assert their aspirations within society. This essay employs a qualitative technique and adopts a feminist theoretical framework. It utilizes McQueen's theory for gender conflict and Petrie and Boggs' theory for characterization, focusing on the film Red Snake Sister in Arms. The manifestations of gender conflict include the pursuit of love, the quest for aspirations, and the confrontation with life's realities. researchers affirm that female characters are portrayed as embodiments of gender conflicts in the film Red Snake Sister in Arms. This is illustrated through the acts of female characters and representations of gender conflicts. This is also exemplified by other characters that oppose the gender battle.